Timor-Leste enables data-driven fisheries management with adoption and integration of PeskAAS - CGIAR Platform for Big Data in Agriculture (2021)
The PeskAAS system was adopted and paid for by the Government of Timor-Leste (GOTL) as part of the annual budget. In providing catch and effort information for the national fishing fleet, it is now the platform for data-driven fisheries decision-making in Timor-Leste, covering about 20 per cent of the national fleet. This system and associated training to maintain and interpret analytics for policy decision making represent significant advances in the capacity of Timor-Leste government to manage their fisheries resources scientifically.